Distinct clusters of bacterial and fungal microbiota in end-stage liver cirrhosis correlate with antibiotic treatment, intestinal barrier impairment, and systemic inflammation - Laura Buttler; David A. Velázquez-Ramírez; Anja Tiede; Anna M. Conradi; Sabrina Woltemate; Robert Geffers; Birgit Bremer; Vera Spielmann; Julia Kahlhöfer; Anke R.M Kraft; Dirk Schlüter; Heiner Wedemeyer; et al. (Gut Microbes)
Decompensated liver cirrhosis (dLC) is associated with intestinal dysbiosis, however, underlying reasons and clinical consequences remain largely unexplored. We investigated bacterial and fungal microbiota, their relation with gut barrier integrity, inflammation, and cirrhosis-specific complications in dLC-patients. Competing-risk analyses were performed to investigate clinical outcomes within 90 days. Samples were prospectively collected from 95 dLC-patients between 2017 and 2022. Quantitative metagenomic analyses clustered patients into three groups (G1–G3) showing distinct microbial patterns. G1 (n = 39) displayed lowest diversity and highest Enterococcus abundance, G2 (n = 24) was dominated by Bifidobacteria, G3 (n = 29) was most diverse and clustered most closely with healthy controls (HC). Of note, bacterial concentrations were significantly lower in cirrhosis compared with HC, especially for G1 that also showed the lowest capacity to produce short chain fatty acids and secondary bile acids. Consequently, fungal overgrowth, dominated by Candida spp. (51.63%), was observed in G1. Moreover, G1-patients most frequently received antibiotics (n = 33; 86.8%), had highest plasma-levels of Zonulin (p = 0.044) and a proinflammatory cytokine profile along with numerically higher incidences of subsequent infections (p = 0.09). In conclusion, distinct bacterial clusters were observed at qualitative and quantitative levels and correlated with fungal abundances. Antibiotic treatment significantly contributed to dysbiosis, which translated into intestinal barrier impairment and systemic inflammation.